2002
DOI: 10.1038/sj.bjc.6600328
|View full text |Cite
|
Sign up to set email alerts
|

Frequent expression of new cancer/testis gene D40/AF15q14 in lung cancers of smokers

Abstract: We found a significant correlation between lung cancer in smokers and the expression of a human gene, D40, predominantly expressed in testis and cancers. In an attempt to clone a novel human gene, we screened a cDNA library derived from a human B cell line and obtained a cDNA clone that we refer to as D40. A search for public databases for sequence homologies showed that the D40 gene is identical to AF15q14. D40 mRNA is predominantly expressed in normal testis tissue. However, this gene is also expressed in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Poorly differentiated lung tumors express D40 more frequently than wellor moderately differentiated ones. In addition, the incidence of D40 expression was significantly higher in tumors from patients who smoke than in those from nonsmokers (Takimoto et al 2002).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Poorly differentiated lung tumors express D40 more frequently than wellor moderately differentiated ones. In addition, the incidence of D40 expression was significantly higher in tumors from patients who smoke than in those from nonsmokers (Takimoto et al 2002).…”
Section: Introductionmentioning
confidence: 91%
“…Previously, we have cloned and reported a human gene, D40, a new cancer/testis gene (Wei et al 1999, Takimoto et al 2002. This gene is expressed predominantly in testis among normal organs and tissues, while it is widely expressed in a variety of cultured human cancer cell lines and primary tumors derived from various tissues and organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic CT genes are among the least studied; the latest report of Kubuschok et al (2004) shows that out of 10 different CT genes analysed, only HOM-TES-14/ SCP-1 and GAGE were expressed in a significant proportion of pancreatic tumour cases (48 and 21%, respectively), SCP-1 (synaptonemal complex protein) is expressed in almost 50% of PDAC specimens (Tureci et al, 1998), whereas D40/CT29 was found expressed in not more than 27% of PDACs (Takimoto et al, 2002). Except for SCP-1, which plays an important role in the alignment of the two homologous chromosomes, in promoting crossing-over events and ensuring chromosome segregation in meiosis (Tureci et al, 1998), the function of the remaining CT genes is completely unknown.…”
Section: Spag1 In Pancreatic Adenocarcinomamentioning
confidence: 99%
“…[22][23][24][25][26] However, investigations encompassing more recently described members of this class and studies addressing the cumulative expression of a set of several CG genes are not available yet. Moreover, previous studies have not correlated CG gene expression to the histological subtype of lung cancer.…”
mentioning
confidence: 99%